Emily Brontë and Aspects of Platonic Attitudes. (3rd July 2019) - Chitham, Edward
Abstract : Dr Johanna Schakenraad reminded us in her 2016 article in Brontë Studies of the incidence in Wuthering Heights of the word 'soul' and some of the contexts in which it is used. Hilary Newman took up the question of death in Wuthering Heights in July 2018. In this article I shall widen the enquiry to consider Emily Brontë's intrinsically Platonic attitude in many matters which she absorbed and developed from the prevailing culture, giving examples from her writing, including poetry, with episodes and examples from her own life. In particular, the blurring of life and death in Wuthering Heights is deeply unfashionable and requires some mediation. I shall not deal in the present article with another influence, Stoicism, nor do I intend to examine subconscious or mythic implications of Emily's usages.